Book Reviews. (1st March 2020) - Mazzoli, Eleonora Maria; McDowell, Stephen D.; Sexton, Max
Custodians of the Internet: Platforms, Content Moderation, and the Hidden Decisions That Shape Social Media, Tarleton Gillespie (2018)New Haven and London: Yale University Press, 304 pp., ISBN 978-0-30017-313-0, h/bk, 30Television in Transition in East Asia, Ki-Sung Kwak (2018)Abingdon: Routledge, 184 pp., ISBN 978-1-13864-798-5, h/bk, £115.00Building Successful and Sustainable Film and Television Businesses: A Cross-national Perspective, Eva Bakoy, Roel Puijk and Andrew Spicer (eds) (2017)Chicago: Intellect, 356 pp., ISBN 978-1-78320-820-3, p/bk, 48